Biosynthesis of Ag nanospheres using waste phoenix dactylifera argonne: a prospective anticancer and antibacterial. (28th August 2019) - Salih, Ban Dawood; Ali, Aisha H; Alheety, Mustafa A; Mahmood, Ahmed Raoof; Karadağ, Ahmet; Ayd𝚤n, Ali
Abstract: In this study, we demon strate the possibility of using the aqueous extract of phoenix dactylifera (palm) argonne (argonne is a curved part in the palm holding the dates) as bio-reducing agent to prepare Ag nanoparticles. The resulting Ag nanoparticles are characterized using the following techniques: UV–vis, FTIR, XRD, EDAX, SEM and TEM. Surprisingly, the results prove that silver sizes ranged from 42 to 45 nanometers with spherical shape and the silver nanospheres also show high stability, no agglomeration for 30 days. Moreover, the ability of these nanospheres (126–7.875 μ g ml −1 ) to inhibit E. coli bacteria was successfully tested. The antibacterial result shows that the MIC is 11.812 μ g ml −1 from silver nanospheres. Moreover, the kinetic study on E. coli growth is also studied to determine the lower incubation time kills E. coli . The effect of 7.875 μ g ml −1 of newly prepared Ag nanospheres on bacterial morphology is determined by the SEM technique for three different incubation times. Furthermore, the anticancer activity of the prepared nanoparticles is evaluated by MTT proliferation assay against prostate cancer cell line ( in vitro ) showing potent anti-tumor effect (TGI value of 8.1 μ g ml −1 ) against PC3 cells.